Pemanfaatan Limbah Padat Cangkang Kerang Simping (Placuna placenta linnaeus) Untuk Pengolahan Limbah Cair Laboratorium - Fitriyani Fitriyani; Heryana Umrah; Khusnul Yaqin (Labor Dasar dan Sentral Universitas Andalas, 2022)
The pollutants contained in laboratory wastewater are phosphate, nitrate and ammonium . This study aims to determine the effectiveness of scallop shells (Placuna placenta linnaeus) as an adsorbent for the mentioned pllutants in laboratory wastewater. The scallop shells used in this study were converted into flour/powder with a particle size of 60 mess and activated at 800Â°C for 4 hours. Variations in the treatment of adding 10 g, 25 g and 50 g of scallop flour each with a contact time of 1 hour and three replications. Sample analysis was performed using the UV-Vis Spectrophotometer method. The results of the ANOVA test analysis showed that the effectiveness of the scallop shell adsorbent in absorbing phosphate waste was not significantly different (pvalue > 0.05) to the various treatments of the adsorbent. The absorption efficiency value of scallop shell adsorbent for heavy treatment on phosphate levels in laboratory waste was 97.60%, while for nitrate waste the absorption efficiency was 37.27%. The different doses of the adsorbent added showed a different 10 g treatment (p value 0.0454 <0.05) from the 25 g treatment but not significantly different from the 50 g treatment (p vaue 0.999 > 0.05). Whereas for ammonia waste there was no adsorption process after adding scallop shell adsorbent. The results showed that scallop shell waste has the potential as an adsorbent in laboratory waste to reduce phosphate and nitrate levels.